3D (.Obj) Image Watermarking and Key Generation Using Dwt Algorithm - Rani, J.Jansi; Anusuya, S.; Senthamilarasi, C. (International journal of innovative technology and exploring engineering, 2019)
Digital media like images ,3D models audio and video can be used to embed signals in digital form. This process is popularly known as Digital Watermarking.The digital watermarking process is done by different methodologies such as steganography and by cryptography. The steganography method is used to hide the data and the cryptography method is used to encrypt the data into desired format. In this paper we proposed the method of cryptography and DWT (Discrete Wavelet Transform) algorithm for hiding the data and to generate a secret key for the data transmission. The data is embedded in a 3D real time object (.obj). The frequency and energy of the image pixel is calculated by DWT algorithm and by doing XOR operation the secret key will be generated by cryptography method. The 3D image is divided by vertical splicing technique. The data is embedded into an image in the form of binary data as 0’s and 1’s.